Expression of vesiculation-related genes is associated with a tumor-promoting microenvironment: a pan-cancer analysis - Westermann, Luisa; Diergaarde, Brenda; Heidegger, Simon; Poeck, Hendrik; Szczepański, Mirosław J.; Reichert, Torsten E.; Spörl, Silvia; Whiteside, Theresa L.; Spoerl, Steffen; Ludwig, Nils (Clinical & Translational Oncology, 2025)
Background: Small extracellular vesicles (sEV) released by tumor cells (tumor-derived sEV; TEX) mediate intercellular communication between tumor and non-malignant cells and were shown to impact disease progression. This study investigates the relationship between the expression levels of the vesiculation-related genes linked to sEV production and the tumor microenvironment (TME). Methods: Two independent gene sets were analyzed, both previously linked to sEV production in various non-malignant or malignant cells. Expression profiles were compared among 28 tumor types listed in the Cancer Genome Atlas (TCGA). Gene expression and survival analysis (GEPIA2), immunogenomic analysis (TISIDB), and genomic analysis (GSCA) were performed. Results: Vesiculation-related genes were overexpressed in tissues of most tumor types compared to healthy tissues, and high expression levels were associated with worse overall survival in cervical squamous cell carcinoma, kidney chromophobe, lower grade glioma, hepatocellular carcinoma, lung squamous cell carcinoma, and pancreatic adenocarcinoma but with improved overall survival in kidney renal clear cell carcinoma. Expression of these signatures correlated with an increased abundance of infiltrating CD4( +) T cells and dendritic cells, a decreased abundance of B cells and eosinophils, and activation of tumor cell apoptosis and epithelial–mesenchymal transition pathways in all tumor types. 17-AAG was identified as a potential drug candidate to target tumors with elevated expression of vesiculation-related genes. Conclusions: Vesiculation-related genes were associated with distinct immunological and genomic landscapes further emphasizing the important role of TEX in cancer progression.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Exosomes; Extracellular vesicles; Tumor microenvironment; Tumor-infiltrating immune cells; Vesiculation-related genes